Studi perbandingan pemberian otonomi asimetris pada keistimewaan Daerah Istimewa Yogyakarta dan kekhususan Provinsi Papua - A Rahman; Ishviati J Koenti; Endang Sulistyaningsih (Kajian Hasil Penelitian Hukum, 2019)
The asymmetric autonomy granting to Special Region of Yogyakarta and Papua Province raises a new problem. In the other hand, the exercise is not maximal. On the other hand, it creates a heartburning to the other region. Base on the those things, the problem can be formulated into two things: the first, how is the comparision of autonomy granted to Special Region of Yogyakarta dan Papua Region? The second, how is the exercise of the autonomy in Special Region of Yogyakarta and the autonomy in Papua Region This Question will be explored by library research method and conceptual and comparative approach. The result of this research is, the first, the special status granted is base on the reason of jurisprudence and the analysis of politics. The second, the exercise of the authority in Special Region of Yogyakarta has exercised well, while in Papua, it has not yet worked at all.